2015
DOI: 10.3390/fi7040500
|View full text |Cite
|
Sign up to set email alerts
|

A Hierarchical Multitier Approach for Privacy Policies in e-Government Environments

Abstract: The appeal of e-Government users to retain control over their personal information, while making use of advanced governmental electronic services through interconnected and interoperable deployments, can be assisted by the incorporation of privacy policy and Preferences documents. This paper addresses the formulation of light-weight and accurate privacy policies, while preserving compliance with underlying legal and regulatory framework. Through the exploitation of existing governmental hierarchies, a multitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Some studies have identified privacy risks or policies for organizations in collecting and processing data (Drogkaris, Gritzalis et al 2015, Kao 2015, some have provided decision support for opening data in general (Zuiderwijk and Janssen 2015), and some have focused on releasing information and data on the individual level (James, Warkentin et al 2015). Nevertheless, there is still limited insight in how organizations can reduce privacy violation risks for open data in particular, and there is no uniform approach for privacy protection (Janssen and van den Hoven 2015 This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have identified privacy risks or policies for organizations in collecting and processing data (Drogkaris, Gritzalis et al 2015, Kao 2015, some have provided decision support for opening data in general (Zuiderwijk and Janssen 2015), and some have focused on releasing information and data on the individual level (James, Warkentin et al 2015). Nevertheless, there is still limited insight in how organizations can reduce privacy violation risks for open data in particular, and there is no uniform approach for privacy protection (Janssen and van den Hoven 2015 This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%